The Effect of Al2O3 Doped and Carbon Coated Li4Ti5O12 on Structures, Morphology and Electrochemical Performance - Priyono, Slamet (Journal of Technomaterial Physics, 2020)
In this research, Li4Ti5O12 anode with doping Al2O3 and carbon coating was made to determine the effect of doping Al2O3 and carbon coating on crystal structure, morphology and electrochemical performance. Li4Ti5O12 anode material consisting of LiOH.H2O and TiO2 was made with various samples of LTO without doping, LTO doped carbon, LTO doping Al2O3 and carbon using the solid state reaction method. All raw materials are mixed and milled using a Planetary Ball Miller for 2 hours then crushed to become a precursor to Li4Ti5O12. The Li4Ti5O12 precursor was sintered at 850Â°C for 4 hours. The final product was characterized using X-Ray Diffraction (XRD) to determine the formation of Li4Ti5O12 phases, Scanning Electron Microscopy (SEM) to analyze the morphology formed, and Cyclic Voltammetry to determine electrochemical performance. The results of XRD characterization were formed in the Lithium Titanium Oxide (Li4Ti5O12), Dilithium Titanate (Li2TiO3), and Rutile (TiO2) phases. The SEM characterization results on LTO doping carbon, LTO doping Al2O3 and carbon showed a coarser texture compared to the LTO without doping which had a fine texture. The electrochemical performance produced in LTO coating carbon has a slender redox peak in the first cycle, this shows that LTO coating carbon has good electrochemical performance compared to the Al2O3 and carbon doping LTO samples.